Practical distributed voltage control method for efficient and equitable intervention of distributed devices - Simon Heslop; Iain MacGill; John Fletcher (IET Smart Grid, 2019)
Growing penetrations of distributed photovoltaic (PV) generation in low-voltage electrical networks are raising new challenges for electricity industry operation. Voltage rise is a particular concern and new distributed voltage management techniques have been proposed in the literature. In this study, a novel distributed voltage control method is presented. The method is designed to be used by both PV systems and controllable loads and uses both a voltage and a power set point to manage control. These set points, along with a voltage sensitivity measure, are then used to control PV system generation and load-shedding. The objective of the control is to keep voltage levels within operational limits with reasonable accuracy. The method is practical; local measurements of net-power and voltage are used with no additional communication infrastructure required. The proposed method is compared to a power set point only and a voltage set point only control method. Results show the proposed method improves on both methods in terms of both voltage accuracy and the equity of intervention.